Physical and optical analysis of cerium doped tellurite glass embedded with copper nanoparticles / Amira Syuhadah Abd. Razak - Abd. Razak, Amira Syuhadah (2020)
Two series of glasses with composition of (85 - x) Te02 - 3MgO - 2Li2C03 - 10Na20 – (x) Ce02 where O.O≤x≤ 2.0 mol % and (84 -y) Te02-3MgO-2Li2C03 - IONa20 - 1.0Ce02 - (y) CuO where 0.25≤y≤ 1.0 mol % glasses system have been studied. The samples were prepared by using conventional melt quenching techniques. The amorphous nature of glass is determined by using X-Ray Diffraction (XRD). The physical properties are measured in terms of density, molar volume and ionic packing density (OPD). Meanwhile the optical analysis is analysed by using the ultraviolet-visible-near infrared (UV-Vis-NIR) and photoluminescence (PL) spectroscopy, respectively. It is found that all glasses are amorphous in nature. The glass density and molar volume with different concentration ofCe02 are found in the range of (4.637 - 4.935) g cm-3 and (29.525 - 31.068) cm3 mol-I, respectively. Whereas, the density and molar volume of the glass containing CuO NPs are found in the range of (4.79 - 4.93) g cm-3 and (29.23 - 30.04) cm3 mol-1 respectively. Meanwhile, UV- Vis - NIR absorption spectra shows absorption peaks centered at 356nm, 418nm and 667nm for series 1, meanwhile peaks centered at 357nm, 412nm and 720nm for series 2. The optical band gap for series 1 and series 2 glasses found ranging from 1.92 eV to 2.74 eV and from 1.71 eV to 2.29 eV respectively. Meanwhile, the Urbach energy was found varies from 1.92 eV to 2.43 eV for glass containing Ce02 and whereas for glass containing Cu NPs ranging from 1.94 eV to 2.02 eV. The SPR revealed located at 800nm of UV-Vis spectra. Luminescence spectra under 356nm excitations between 5d → 4FI levels of Ce3+ ions revealed five peaks of emission bands of cerium doped glass which are centered at 475nm, 520nm, 550nm, 560nm and 660nm. Meanwhile glass containing CuO NPs centered at 460nm, 520nm, 550nm, 565nm and 660nm.